Causes and consequences of feelings - Berkowitz, Leonard, 1926- (Studies in emotion and social interaction., 2000)
Although is is well known that people's feelings can often influence what they remember, think and do, investigations of these effects are relatively new. Summarizing much of what has been learned in past decades, this book looks at how feelings arise, and how they can affect thought and actions.